Pengaruh Penerapan Model Pembelajaran RADEC (Read, Answer, Discuss, Expain, Create) Berbantuan Media 3D Printing Terhadap Kemampuan Berpikir Kritis Siswa Kelas XI SMA Negeri 17 Luwu - Muhajirah Yunus, Nur; Ramadhani, Fitra; Khaerati; Sohriati, Eva; Syakur, Akhmad (Universitas Cokroaminoto Palopo, 2025)
This study aims to determine the effect of the application of the RADEC (Read, Answer, Discuss, Explain, Create) learning model assisted by 3D printing media on the critical thinking skills of class XI students of SMA Negeri 17 Luwu. This type of research is a quasi-experimental study with a non-equivalent control group design. The population in this study were all 46 students of class XI MIPA of SMA Negeri 17 Luwu. The sampling technique used was total sampling, by selecting class XI MIPA 2 as the experimental class with 21 students and XI MIPA 1 with 24 students as the control class. The research instruments used were pretest and posttest questions to measure students' critical thinking skills, as well as observation sheets for the implementation of learning. Data collection techniques in this study include descriptive analysis and inferential analysis. The descriptive statistical test of the experimental class obtained a pretest score of 40.19 with a low category while the control class obtained a pretest score of 40.25 with a low category. After being given treatment, the posttest score of the experimental class was 87.24 with a very high category while the control class was 80.25 with a high category. The inferential statistical test yielded a value of 0.001 < 0.05, indicating a significant effect of the RADEC learning model supported by 3D printing on students' critical thinking skills. Therefore, the combination of the RADEC model and 3D printing can be an effective strategy for improving students' critical thinking skills in biology learning.